Anesthesia for adult major spine surgery - Lima, Gisela Marques (Journal of the Portuguese Society of Anesthesiology, 2018)
Objective - Spine surgery has evolved over the past two decades into a multidisciplinarity of medical areas, including neurosurgery, orthopedics, pain medicine and neuroradiology. The pathology of the spine is vast and encompasses patients who are increasingly older and with more comorbidities, while there are several surgical techniques to which the anesthesiologist has to adapt. Material and Methods - A comprehensive review of the Medline, Embase and Cochrane databases was performed using the following keywords: anesthesia, spinal surgery, cervical lesion, neuromonitoring, perioperative vision loss and vertebro-medullary trauma. Results - The main complications of spinal surgery are: paralysis, massive hemorrhage, infection, positioning, postoperative respiratory complications, and chronic pain. Some of the aspects that the anesthesiologist has to take into account include the approach of the airway, monitoring and drugs, patient positioning, blood-sparing techniques and possible complications. Discussion and Conclusions - Successful results following major spinal surgery depend on an appropriate and considered anesthetic technique. The incidence of complications can be reduced by attention to detail and a good understanding of surgical specificities.